Sengketa Budaya Sasando di Forum Internasional Dalam Perspektif Hukum Internasional dan Hak Kekayaan Intelektual (The Cultural Dispute Over Sasando In International Forums From The Perspective Of International Law And Intellectual Property Rights) - Triadi, Irwan; Ledewedjo, Jessica Leonita Anabel; Panjaitan, Rachel Netanya; Lubis, William Haposan; Fadhila, Rasya Aika (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Sasando is a traditional musical instrument originating from East Nusa Tenggara that holds significant cultural and historical value, serving as a symbol of Indonesia’s national identity. In 2021, reports emerged that Sri Lanka attempted to register Sasando as part of its cultural heritage with the World Intellectual Property Organization (WIPO), raising concerns over transnational cultural claims. This case highlights the urgency of protecting cultural heritage through international legal instruments, particularly within the framework of Intellectual Property Rights (IPR). This study aims to examine how international law can safeguard traditional cultural expressions such as Sasando and to what extent international IPR mechanisms can prevent unilateral claims by other countries. Using a normative juridical approach supported by case studies and analysis of international conventions—particularly the 2003 UNESCO Convention and WIPO’s role—the findings reveal that while legal frameworks exist, cultural heritage protection remains suboptimal without active registration, documentation, and diplomatic efforts by the country of origin. Therefore, countries like Indonesia must proactively engage in international mechanisms to protect and uphold their cultural heritage against illegitimate claims at the global level.